'The Dark Corners of the World': TWAIL and International Criminal Justice - Reynolds, John; Xavier, Sujith (2016)
Despite international criminal law’s historically contingent doctrines and embedded biases,Third World self-determination movements continue to be enticed by international criminal justice as a potentially emancipatory project. This article seeks to peer inside the structural anatomy of the international criminal law enterprise from a vantage point oriented to the global South. It reflects broadly on discourses of international criminal law and its exponents as they relate to the global South, and explores one particularly contentious issue in the politics of international criminal law - that of operational selectivity. Redressing such selectivities as they arise from geopolitical biases is an important first step for any reconstruction of the field of international criminal justice. The article emphasizes, however, the need to also look beyond the problems of unequal enforcement, to reconceptualize the forms of violence criminalized at the design level.We ask whether, given certain colonial features, the premise and promise of international criminal justice can - for self-determination struggles or anti-imperial movements in the global South - be anything more than illusory. Drawing on the perspectives of Third World Approaches to International Law (TWAIL), the article concludes with some thoughts on what ‘TWAILing’ the field of international criminal justice might entail.
Keywords: Sujith Xavier